Molecular investigation of the presence of (pslD, pslA, rhlR) genes in Pseudomonas aeruginosa isolated from burns and wounds - E. Ibrahim, Marwa; Jawad Al Zubaidi, Saba J. (ASJ - Academic Science Journal, 2025)
Background: Pseudomonas aeruginosa is one of the most common Gram-negative bacteria responsible for outbreaks of infection and morbidity in hospitals. The difficulty in treating them lies in their possession of a wide range of virulence factors in addition to their ability to have natural and acquired resistance to antibiotics especially the multi-drug resistance (MDR) ones. Material and Methods: 114 samples were collected and isolated from burns and wounds patients hospitalized in Baquba Teaching Hospital, during the period from September to December 2022. These isolates were diagnosed using conventional diagnostic methods, microscope diagnosis, and biochemical tests, and then the final diagnosis was made using the VITEK2 compact system device. Results: 43 isolates 42% were obtained from the total collation samples of P. aeruginosa. A test was conducted to detect the ability to from biofilms, and the results were as follows: (Strong adherent 41%, n=7), (Moderately adherent 23%, n=4), (Weakly adherent 35%, n=6), and they were tested for sensitivity towards 12 antibiotics, and the results were as follows: AMC 96%; CAZ 100%; CTX 100%; CRO 100%; FEP 75%; MEM 76%; AK 82%; TOB 76%; GN 70%; E 94%; PB 23%; CIP 47%. 17 of them were isolates with multidrug resistance (MDR). Sequence analysis was used to detect the presence of (pslD, pslA, rhlR) genes in 17 isolates of P. aeruginosa, and the obtained results were as follows: the presence of the pslD gene at arte of (94%; n=16), the pslA gene at rate of (100%; n=17), and the rhlR gene at rate of (100%; n=17).